Análisis de la implementación de tecnologías para la disminución del impacto ambiental en los procesos de reconversión industrial para la estación Acacias de Ecopetrol (2022)
The main objective of this work was to propose methodologies for the measurement of environmental indicators after the process of industrial reconversion in the Acacias Station under the principles of green economy. This was done through a series of bibliographical queries and relevant technical information.